A survey of specialist paediatric dental services in Sweden: results from 2003, and trends since 1983 - G. KLINGBERG, G. DAHLLÖF, A.-L. ERLANDSSON, M. GRINDEFJORD, U. HALLSTRÖM-STALI (Paediatric Dentistry, 2006)
In Sweden, paediatric dentistry was recognized as a dental speciality in 1963. According to the Dental Health Act of 1974, the provision of free comprehensive dental care, including orthodontics for all children aged 0–19 years, is the responsibility of the county health authorities.